ANALISIS PENGARUH PRODUK DOMESTIK REGIONAL BRUTO (PDRB) SEKTOR PERTANIAN TERHADAP PERTUMBUHAN EKONOMI DI KABUPATEN ACEH SELATAN - Irwan Suharmi (Universitas Teuku Umar, 2018)
The problem of this research is how is the influence of GRDP (gross regional domestic product) of pertanin sector on economic growth in South Aceh regency, the purpose to be achieved in this research is to know the influence of GRDP (gross regional domestic product) agricultural sector on economic growth in regency South Aceh.Based on the results of research conducted by the author,the writer has been able to know the effect of GDP (gross regional domestic product) agricultural sector on economic growth in the district of South Aceh,this is proven results of free variable analysis with the value of GDP (gross regional domestic product) sector agriculture 1,981 > 1,860 so it can be interpreted that GRDP (gross regional domestic product) agricultural sector effect on economic growth.Thus this also indicates that the hypothesis proposed in this research can be received.Gross regional domestic product (gross regional domestic product) gross domestic product (gross regional domestic product) gross r 0,809 positively explained that there is a close relationship between PDRB (product domestic gross regional) agricultural sector 80,9 % ,the coefficient of determination (r2) of 0.809 can be interpreted that economic growth in south aceh district is 80,9 % caused by gross regional domestic product (GRDP) of agricultural sector economic growth South Aceh.Keywords: GRDP, Gross Regional Domestic Product, Agriculture, Sector, Economic Growth.